Intelligent Image Processing System Based on Virtual Painting - Samira Abdul-Kader Hussain (Journal La Multiapp, 2022)
Image processing and artificial intelligence have come so far in the age of technology that they are now used in every field. AI is meant to help people do their jobs better and with less help. Virtual painting is a clever tool that lets us paint by just moving our hands. This app uses hand tracing and finger movement recording to show marks. With this program, we can open the camera on our computer or laptop and draw with our hands, colored pens, or pens we made ourselves. Image processing is used to figure out how the hand is moving. This turns the person in front of the camera into a great illustrator who can pick out colors and draw in similar directions on the screen. OpenCV, which is the brain of the system, and Media Pipe have been added to this application.